2019
DOI: 10.1093/icc/dtz029
|View full text |Cite
|
Sign up to set email alerts
|

Lenders’ selection capabilities, patent quality, and the outcome of patent-backed loans

Abstract: In this paper, we investigate the phenomenon of patent collateralization by empirically focusing on the factors that affect the outcome of the collateralization process. In particular, we want to examine to what extent patent quality, lenders’ characteristics, as well as lenders’ selection capabilities (i.e. in identifying high-quality patents) affect the likelihood of observing a security interest release. We identify the patents recorded in security agreements and their release from the USPTO Patent Assignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In comparison, the lender has an information disadvantage relative to the borrower in terms of whether a loan will default, and the lender bears the loss if the pledged patent cannot be liquidated. Due to these reasons, and consistent with prior research (e.g., Caviggioli et al, 2020; Fischer & Ringler, 2014; Hochberg et al, 2018), we adopt the lender's view in developing our arguments.…”
Section: Theory and Hypothesesmentioning
confidence: 55%
See 2 more Smart Citations
“…In comparison, the lender has an information disadvantage relative to the borrower in terms of whether a loan will default, and the lender bears the loss if the pledged patent cannot be liquidated. Due to these reasons, and consistent with prior research (e.g., Caviggioli et al, 2020; Fischer & Ringler, 2014; Hochberg et al, 2018), we adopt the lender's view in developing our arguments.…”
Section: Theory and Hypothesesmentioning
confidence: 55%
“…Even after a patent is pledged, the legal ownership of the patent and the right to use the patent, continues to be held by the borrower (i.e., the patent owner), unless the loan defaults, and the rights on the collaterals are returned to the original owner by the lender when the agreement terminates (Caviggioli, Scellato, & Ughetto, 2020; Marco, Myers, Graham, D'Agostino, & Apple, 2015). According to Caviggioli et al (2020), only about 20% of pledged patents in their sample were not (or have not been) returned to the original owner, including recent agreements that are still at risk of being released in the future and termination cases that were not reported to the United States Patent and Trademark Office (USPTO) 3 . In other words, pledging a patent does not affect the borrower's legal ownership or their right to use the patent, unless the loan defaults.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, patents with low knowledge breadth limit potential purchasers in specific technology industries. Thus, if a debtor that uses patents with a high knowledge breadth as collateral defaults, the creditor can find more potential purchasers, which makes it easier for creditors to liquidate the patents to reduce transaction costs and recover losses (McCarthy and Ruckman, 2017;Caviggioli et al, 2020;Mann, 2018). Consequently, we hypothesise that: H1.…”
Section: Knowledge Breadth and Patent Pledgesmentioning
confidence: 98%
“…Researchers found that knowledge breadth provides the ability to integrate diverse information to generate new ideas, adapt to technological changes and seize market opportunities (Boh et al , 2014). Therefore, patents with a high knowledge breadth have high strategic importance to patent owners and transactional attractiveness to potential buyers, as both are willing to exploit these resources to enhance their competitive advantage and performance (Lerner, 1994; Caviggioli et al , 2020; Katila and Ahuja, 2002). Conversely, knowledge depth captures the analytical sophistication and cognitive complexity of knowledge in key fields (Moorthy and Polley, 2010; Bierly and Chakrabarti, 1996; Zhou and Li, 2012).…”
Section: Theory and Hypothesesmentioning
confidence: 99%